Pengaruh profitabilitas dan likuiditas terhadap nilai perusahaan dengan struktur modal sebagai variabel intervening - Puri, Ellisa Tiara; Lisiantara, G. Anggana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Company value is an important factor for investors and creditors in assessing the suitability of a company as a place to invest capital or a source of debt. Company value can be influenced by various factors. This research aims to examine the effect of profitability and liquidity on company value through capital structure. This research was conducted using a quantitative approach. The population of this research is manufacturing companies from the consumer goods industrial sector listed on the Indonesia Stock Exchange in 2019–2021. The sample in this study was determined using a purposive sampling technique, so a sample of 113 companies was obtained. The data in this research uses secondary data from the website www.idx.co.id. The data analysis technique used in this research uses multiple regression analysis techniques with SPSS. This research shows the results that ROA has no effect on PBV, CR has an effect on PBV, ROA has an effect on DER, CR has no effect on DER, DER has an effect on PBV, ROA has an effect on PBV through DER, and CR has an effect on PBV through DER.